2014
DOI: 10.3177/jnsv.60.78
|View full text |Cite
|
Sign up to set email alerts
|

Retinol Status and Expression of Retinol-Related Proteins in Methionine-Choline Deficient Rats

Abstract: Vitamin A (retinol) plays an important role in vision and has pleiotropic functions in immune response, hematopoiesis, fertility, cell differentiation, growth, and morphogenesis (1). Both retinol deficiency and excessive doses of retinol cause malformations in the embryos of many vertebrate species, demonstrating that retinol plays an important role in embryogenesis. Retinoic acids, derivatives of retinol, act as the ligands of retinoic acid receptors (RAR) and retinoid X receptors (RXR), which are members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In the current study, BCMO expression in the testes of DHEA-fed rats was higher than in controls, which indicated opposite regulation to that in the liver and intestine. In previous studies, we reported that BCMO expression was higher in the testes of streptozotocininduced type 1 diabetic rats and methionine-cholinedefi cient NAFLD model rats, both of which had lower plasma retinol levels than the controls (16,17). These previous results are in agreement with the fi ndings of the current study, and suggest that the testes tissue of DHEA-treated rats might sense the need for retinol due to the reduced plasma retinol levels.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the current study, BCMO expression in the testes of DHEA-fed rats was higher than in controls, which indicated opposite regulation to that in the liver and intestine. In previous studies, we reported that BCMO expression was higher in the testes of streptozotocininduced type 1 diabetic rats and methionine-cholinedefi cient NAFLD model rats, both of which had lower plasma retinol levels than the controls (16,17). These previous results are in agreement with the fi ndings of the current study, and suggest that the testes tissue of DHEA-treated rats might sense the need for retinol due to the reduced plasma retinol levels.…”
Section: Discussionsupporting
confidence: 83%
“…In comparison, Zucker rats with obesity and dyslipidemia showed lowered LRAT expression in the liver, which was associated with increased plasma retinol levels (20). These fi ndings suggest that altered LRAT expression may be associated with retinol status (16). In the current study, hepatic expression of the gene encoding LRAT is decreased by DHEA administration, which might lead to lowered retinol levels in the liver.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Retinol and its derivative, retinoic acid, have critical roles in liver regeneration and pathogenesis including inflammation, steatosis, fibrosis, cirrhosis and cancer (Park et al, 2012). Retinol as well as cellular retinoic acid binding proteins and retinol-metabolizing enzymes are stored in HSCs (Miyazaki et al, 2014). During the fibrotic process, hepatic stellate cells are activated and lose their lipid drops which store retinol (de Paula et al, 2010).…”
Section: Discussionmentioning
confidence: 99%